Homogeneous antibody-drug conjugates: DAR 2 anti-HER2 obtained by conjugation on isolated light chain followed by mAb assembly. Issue 1 (1st January 2020) - Farràs, Mercè; Miret, Joan; Camps, Marc; Román, Ramón; Martínez, Óscar; Pujol, Xavier; Erb, Stéphane; Ehkirch, Anthony; Cianferani, Sarah; Casablancas, Antoni; Cairó, Jordi Joan
ABSTRACT: Despite advances in medical care, cancer remains a major threat to human health. Antibody-drug conjugates (ADCs) are a promising targeted therapy to overcome adverse side effects to normal tissues. In this field, the current challenge is obtaining homogeneous preparations of conjugates, where a defined number of drugs are conjugated to specific antibody sites. Site-directed cysteine-based conjugation is commonly used to obtain homogeneous ADC, but it is a time-consuming and expensive approach due to the need for extensive antibody engineering to identify the optimal conjugation sites and reduction – oxidation protocols are specific for each antibody. There is thus a need for ADC platforms that offer homogeneity and direct applicability to the already approved antibody therapeutics. Here we describe a novel approach to derive homogeneous ADCs with drug-to-antibody ratio of 2 from any human immunoglobulin 1 (IgG1 ), using trastuzumab as a model. The method is based on the production of heavy chains (HC) and light chains (LC) in two recombinant HEK293 independent cultures, so the original amino acid sequence is not altered. Isolated LC was effectively conjugated to a single drug-linker (vcMMAE) construct and mixed to isolated HC dimers, in order to obtain a correctly folded ADC. The relevance of the work was validated in terms of ADC homogeneity (HIC-HPLC, MS), purity (SEC-HPLC), isolated antigen recognition (ELISA) and biological activity (HER2-positive breast cancer cells cytotoxicity assays).